Understanding social attachment as a window into the neural basis of prosocial behavior - Berendzen, Kristen M. (Frontiers in Neurology, 2023)
The representation and demonstration of human values are intimately tied to our status as a social species. Humans are relatively unique in our ability to form enduring social attachments, characterized by the development of a selective bond that persists over time. Such relationships include the bonds between parents and offspring, pair bonds between partners and other affiliative contacts, in addition to group relationships to which we may form direct and symbolic affiliations. Many of the cognitive and behavioral processes thought to be linked to our capacity for social attachment—including consolation, empathy, and social motivation, and the implicated neural circuits mediating these constructs, are shared with those thought to be important for the representation of prosocial values. This perspective piece will examine the hypothesis that our ability to form such long-term bonds may play an essential role in the construction of human values and ethical systems, and that components of prosocial behaviors are shared across species. Humans are one of a few species that form such long-term and exclusive attachments and our understanding of the neurobiology underlying attachment behavior has been advanced by studying behavior in non-human animals. The overlap in behavioral and affective constructs underlying attachment behavior and value representation is discussed, followed by evidence from other species that demonstrate attachment behavior that supports the overlapping neurobiological basis for social bonds and prosocial behavior. The understanding of attachment biology has broad implications for human health as well as for understanding the basis for and variations in prosocial behavior.